Research dissemination and PhD thesis format at a South African university: The impact of policy on practice. Issue 5 (3rd September 2018) - Odendaal, Albi; Frick, Liezel
ABSTRACT: The dissemination of doctoral research is a crucial ethical, financial and status issue for universities worldwide. The publication based thesis (PBT) may encourage dissemination, but is still in definitional flux at many institutions, particularly in South Africa, especially regarding how many articles are required and the publication status of these articles. We analysed and compared the formats and publication rates of 1128 of the 1141 doctoral theses published at a South African research intensive university over a 7 year period (2008–2014). We present a theoretical frame that considers publication as independent of format. Unpublished monographs account for 41.22% and published PBT for 26.86% of the sample. Monographs where material has been published and PBT with no publications, account for 20.39% and 11.52% of the sample respectively. The article argues that these unique findings are a result of institutional policy directives aimed at addressing the specific social environment of the country.